Respons Hematologi Itik Pengging yang Diberi Tepung Daun Kelor (Moringa oleifera. Lam) Sebagai Imbuhan Pakan - Kasiyati, Kasiyati; Djaelani, Muhammad Anwar; Sunarno, Sunarno (Jurnal Veteriner; Vol 22 No 1 (2021)DO - 10.19087/jveteriner.2021.22.1.8, 2021)
Pengging ducks are one breed of Indonesia’s local duck has superior potential. This study was designed to evaluate the hematological parameters of  Pengging ducks fed Moringa leaf meal as a feed additive. The data were obtained from a total of 80 female Pengging ducks of 35 weeks old were assigned into a completely randomized design and each experimental unit consisted of 4 replications. The treatment group consisted of basal fed without added Moringa leaf meal (control), basal fed added with 2.5, 5, 7.5, and 10% Moringa leaf meal. Data analyzed using one-way ANOVA. The results showed that the addition of Moringa leaf meal gave same effect (P>0.05) on the number of erythrocytes, hemoglobin, hematocrit, mean corpuscular volume (MCV), and mean corpuscular hemoglobin (MCH). However, the mean corpuscular hemoglobin concentration (MCHC) increased (P<0,05) to 15.91% at 5% moringa leaf meal. The number of leukocytes was lower (P<0.05) by 42.01% at 7.5% moringa leaf meal. Leukocyte differentials, the ratio of H:L, and trombocytes did not significant difference (P>0.05) between treatments. In conclusion, the Moringa leaf meal as a feed additive did not change the hematological parameters and could be increasing the health status of layer Pengging ducks.